Basilic vein transposition for unsuitable upper arm hemodialysis needle access segment may attenuate concurrent hand ischemia. Issue 3 (8th March 2018) - Gerrickens, Michael W. M.; Vaes, Roel H. D.; Govaert, Bastiaan; Teijink, Joep A. W.; Scheltinga, Marc R.
Abstract: Introduction: Some hemodialysis patients with a brachial arteriovenous fistula (AVF) have an unsuitable upper arm needle access segment (NAS) necessitating basilic vein transposition (BVT). It was frequently observed that a portion of these patients spontaneously experienced a warmer and less painful dialysis hand after BVT. Aim of this study was to determine whether BVT for an inadequate NAS attenuated hemodialysis access‐induced distal ischemia in patients with a brachial AVF. Methods: Patients with a brachial AVF and an unsuitable NAS also reporting hand ischemia and scheduled to undergo BVT between 2005 and 2016 in a single facility were studied. Hand ischemia was graded as proposed in a 2016 consensus meeting. Hand ischemic questionnaire (HIQ‐) scores (0 points, no ischemia—500 points, maximal ischemia), digital brachial index (DBI, ischemia <0.6) and access flow (mL/min) before and after BVT were compared. The cephalic vein and all side branches of the basilic vein were ligated during the BVT. Findings: Ten patients were studied (8 males, 61 [54–75] years). BVT was performed 8 [4–10] months following the initial AVF construction. HIQ‐scores dropped from 220 [71–285] to 9 [0–78] (P = 0.043) postoperatively, whereas DBI increased from 0.51 [0.39–0.67] to 0.85 [0.68–0.97] (P = 0.012). DBI and HIQ‐scores were inversely correlated ( R 2 =71%, P = 0.001). Access flows dropped significantly (Flowpre 1120 mL/min [1100–2300] vs. Flowpost 700 mL/min [600–1760]; P = 0.018). Surgery‐associated complications were absent and dialysis continued uninterruptedly. Eight patients reported total recovery from hand ischemia six weeks postoperatively. Discussion: Basilic vein transposition for an unsuitable upper arm needle access segment may attenuate hand ischemia in patients with a brachial AVF previously reporting hemodialysis access‐induced distal ischemia.